(untitled) (Annals of Medical Research, 2021)
Aim: This study was planned to investigate the relationship between trunk muscular endurance, balance, and functional level in individuals with chronic low back pain.Material and Methods: Sixty-three individuals, aged 18-65 years and having chronic low back pain for the last six months, were included in the study. Sociodemographic data of the individuals were recorded. The static and dynamic endurance of trunk muscles was evaluated by the curl-up test and modified Sorenson test. In order to evaluate the dynamic balance, the Timed Up and Go test was performed. The functionality level related to the low back pain of individuals was evaluated by the Oswestry Low Back Pain Disability Questionnaire.Results: Forty-one female (65%) and twenty-two male (35%) individuals were included in the study. The mean age of the individuals was 40.50 ± 16.75 years, and the mean body mass index was 26.51 ± 5.34 kg/m2. A moderate negative correlation was found between trunk flexor and extensor muscle endurance with both dynamic balance and functional level (p0.05).Conclusion: It was determined that there is a significant relationship between balance, trunk muscular endurance, and functional level. The presence of this relationship may guide the planning of exercise therapy in individuals with chronic low back pain.